Petrologia e geocronologia U-Pb do plúton granítico Serra da Rajada, porção central do domínio Rio Piranhas - Seridó, Província Borborema, NE do Brasil - Costa, Alan Pereira da (2015)
The ediacaran plutonic activity related to the Brasilian/Pan-African orogeny is one of the most important geological features in the Borborema Province, represented along its extension by numerous batholiths, stocks, and dikes.The object of this study, the Serra Rajada Granitic Pluton (SRGP), located in the central portion of the Piranhas-Seridó River Domain is an example of this activity. This pluton has been the subject of cartographic, petrographic, geochronological and lithogeochemical studies and its rocks were characterized by two facies. First, the granitic facies were described as monzogranites consisting of K-feldspar, plagioclase (oligoclase - An23-24%), quartz and biotite (main mafic) and opaque minerals such as titanite, allanite, apatite, and zircon as accessories. Alteration minerals are chlorite, white mica and carbonate. Second, the dioritic facies consist of rocks formed by quartz diorite containing plagioclase (dominant mineral phase), quartz and K-feldspar. Biotite and amphibole are the dominant mafic minerals; and titanite, opaque minerals, allanite, zircon and apatite are the accessories. However, previous geological mapping work in the region also identified the presence of other lithostratigraphic units. These were described as gneisses and migmatites with undifferentiated amphibolite lenses related to the Caicó Complex (Paleoproterozoic) and metasedimentary rocks of the Seridó Group (Neoproterozoic) composed of paragneiss with calc-silicate lenses, muscovite quartzite and biotite schist (respectively, the Jucurutu formations, Equador and Seridó), the host rocks for the SRGP rocks. Leucomicrogranite and pegmatite dikes have also been identified, both related to the end of the Ediacaran magmatism and colluvial- eluvial and alluvial deposits related to Neogene and Quaternary, respectively. Lithogeochemical data on the SRGP granite facies, highlighted quite evolved rocks (SiO2 69% to 75%), rich in alkalis (Na2O+K2O ≥ 8.0%), depleted of MgO (≤ 0.45%), CaO (≤ 1.42%) and TiO2 (≤ 0.36%) and moderate levels of Fe2O3t (2.16 to 3.53%). They display transitional nature between metaluminous and peraluminous (predominance of the latter) with sub-alkaline/monzonitic (High K calcium-alkali) affinity. Harker diagrams show negative correlations for Fe2O3t, MgO, and CaO, indicating mafic and plagioclase fractionation. REE spectrum shows enrichment of LREE relative to heavy REE (LaN/YbN = 23.70 to 10.13), with negative anomaly in the Eu (Eu/Eu* = 0.70 to 0.23), suggesting fractionation or accumulation in the feldspars source (plagioclase). Data integration allows to correlate the SRGP rocks with those described as Calcium-Alkaline Suite of equigranular High K. The crystallization conditions of the SRGP rocks were determined from the integration of petrographic and lithogeochemical data. These data indicated intermediate to high conditions of ƒO2 (mineral paragenesis titanite + magnetite + quartz), parent magma saturated in H2O (early biotite crystallization), tardi-magmatic processes of fluids rich in ƒCO2, H2O and O2 causing part of the mineral assembly to change (plagioclase carbonation and saussuritization, biotite chloritization and opaques Sphenitization). Thermobarometrical conditions were estimated based on geochemical parameters (Zr and P2O5) and CIPW normative minerals, with results showing the liquidus minimum temperature of about800°C and the solidus temperature of approximately 700°C. The final/minimum crystallization pressure are suggested to be between 3 and 5 Kbar. The presence of zoned minerals (plagioclase and allanite) associated with lithogeochemical data in bi-log diagrams for Rb vs. Ba and Rb vs. Sr suggest the role of fractional crystallization as the dominant process in the magmatic evolution of SRGP. U-Pb Geochronological and Sm-Nd isotope studies indicated, respectively, the crystallization age of biotite monzogranite as 557 ± 13 Ma, with TDM model age of 2.36 Ga, and εNd value of -20.10 to the crystallization age, allowing to infer paleoproterozoic crustal source for the magma.